Production and characterization of sustainable vermimanure derived from poultry litter and rice straw using tiger worm Eisenia fetida. (February 2023) - Srivastava, P.K.; Singh, A.; Kumari, S.; Arora, S.; Choubey, A.K.; Sinha, A.S.K.
Graphical abstract: Highlights: Potential vermimanure have been obtained using poultry litter and rice straw. Growth performance of earthworms in treated groups supported bioconversion process. Various analytical tools elucidated the structure of the nutrients of vermimanure. Ash, decomposition, moisture levels overall raised by 218, 258, 159 % respectively. C/N ratio and electrical conductivity index confirmed the vermimanure maturity. Abstract: Poultry litter (PL) and rice straw (RS), commonly available waste materials, pose severe threat to environment, if not properly managed. As viable waste treatment method, vermi-transformation of PL into enriched vermimanure was done using RS and cow dung (CD) with different feedstocks (FS) combinations like FS0(CD without earthworm), FS1(CD), FS2(1CD: 1RS), FS3(1CD: 1PL) and FS4(1CD: 1RS: 1PL) for 110 days. Increased growth performance (P < 0.05) of Eisenia fetida, macronutrient levels, and a consistently lower carbon-to-nitrogen ratio (C/N) emphasize the importance of RS and PL in the vermimanuring process. Several analytical techniques have revealed the presence of functional groups, nitrate (NO3 – ), phosphate (PO4 3− ), and potassium ions (K + ) as well as the high porosity of the matured vermimanures. Therefore, using earthworms, the feedstock FS4(1CD: 1RS: 1PL) could be successfully biotransformed into sustainable manure lowering the usage of chemical fertilizers and rice straw burning.